Abnormal Audit Delay and Earnings Quality in Nigerian Banking - Alexander Olawumi Dabor; Benjamin David Uyagu (Faculty of Economics, Universitas Sriwijaya, 2018)
The objective of this study is to ascertain the relationship abnormal audit delay and earnings quality in the Nigeria. The study focused on the Nigerian banking sector. The Ordinary Least Square statistical technique was adopted. Eleven banks were selected using the simple random sampling technique. The period under review is eleven years from 2005-2015. The results showed that earnings quality has a negative relationship with abnormal audit delay. The study recommended that management should be prohibited from constant changing of accounting calculation that can cause material discrepancy between the auditor and client regarding accounting practices.